Price Regulation and Parallel Imports of Pharmaceuticals - Kurt R. Brekke; Tor Helge Holmås; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper studies the effects of price regulation and parallel imports in the on-patent pharmaceutical market. In a theory model where the producer price is subject to bargaining between the brand-name producer and a distributor, we show that the effects of stricter price regulation crucially depend on whether the producer faces competition from parallel imports. While parallel imports improve the bargaining position of the distributor, price regulation counteracts this effect and may even be pro.table for the producer. We test the implications of our model on a unique dataset with information on sales and prices at both producer and retail level for 165 substances over four years (2004-7). We show that stricter price regulation reduces competition from parallel imports, and has no (strictly negative) effect on producer profits in the presence (absence) of parallel imports. Our results suggest that price regulation might improve static efficiency without being harmful for dynamic e ciency in the presence of parallel imports.
Keywords: I11; I18; L13; L51; L65; 330; pharmaceutical market; price regulation; parallel imports